2017
DOI: 10.1155/2017/1209360
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Significance of Neuroligin-1 and Neurexin II in the Enteric Nervous System of Embryonic Rats

Abstract: Aim. To investigate the abundance of neuroligin-1 and neurexin II in the enteric nervous system (ENS) of rats on different embryonic days and to explore their potential significance. Methods. The full-thickness colon specimens proximal to the ileocecal junction of rats on embryonic days 16, 18, and 20 and of newborns within 24 hours (E16, E18, E20, and Ep0) were studied, respectively. qRT-PCR was applied for detecting the expressions of neuroligin-1 and neurexin II on mRNA, and western blotting was employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…We have repeated our previous studies [13,14] and confirmed that gene dysplasia of NLs and FN are associated with HSCR. HSCR is divided into three segments:…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We have repeated our previous studies [13,14] and confirmed that gene dysplasia of NLs and FN are associated with HSCR. HSCR is divided into three segments:…”
Section: Resultssupporting
confidence: 82%
“…We have found a temporal trend in the abnormal expression of FN, neuroligin-1 (NL1) and neuroligin-2 (NL2) in the diseased intestine of children with HSCR. [13,14] These pieces of evidence led us to hypothesize that the abnormal development of FN, NL1 and NL2 may lead to intestinal lesions but does not explicitly indicate whether there is a real interaction between FN and NLs. Therefore, we further investigated the expression of FN, NL1 and NL2 on different embryonic days and the relationship between them and confirmed the interaction between FN and NLs in this study.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify potential mechanisms underlying GI dysfunction in neuroligin‐3 linked autism, we characterized expression of neuroligins and their binding partners, the neurexins, in the mouse GI tract. Neuroligins and neurexins are expressed in the rodent [Leembruggen et al, ; Wang et al, ] and human [Wang et al, ; Yang et al, ; Zhang et al, ] GI tract; however, little is known about the functional contribution of neuroligin‐3 expression in the GI tract. Nlgn1 , Nlgn2 , Nlgn3 , Nrxn1 , and Nrxn2 mRNAs are predominantly expressed in myenteric plexus‐enriched preparations of both duodenum and colon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These mutations include genes encoding neuroligins, a group of four postsynaptic adhesion molecules (neuroligins‐1 to 4) and their extracellular and intracellular binding partners, neurexins and SHANK3 [Sudhof, ]. Expression of genes encoding several of these proteins is reported in the GI tract [Wang et al, , ; Yang et al, ; Zhang et al, ]; however a systematic analysis of expression in both the small and large intestine and, of particular interest, in neuronal enriched samples is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting analysis was performed as previously described. [7] Blots were incubated overnight at 4ºC with the following primary antibodies:…”
Section: Western Blottingmentioning
confidence: 99%